RETRACTED: Effects of Forestry on Carbon Emissions in China: Evidence From a Dynamic Spatial Durbin Model - Li, Zaijun; Mighri, Zouheir; Sarwar, Suleman; Wei, Chen (Frontiers in Environmental Science, 2021)
Research proved the significance of forests in controlling carbon emission however, our research shed light on the management of existing forests to combat climate change. To examine the role of forestation and forest investment activities, dynamic spatial techniques are used for 30 provinces of China. The results suggest that forest investment and management not only reduce carbon locally but also in neighboring provinces. Furthermore, the findings of current study confirmed that forest investment are the most viable practices to control carbon emission in China instead of just increasing the forest area. Reforms regarding the management of forests would be a good policy for pollution reduction along with the employment generation side by side.